Hubungan Tingkat Pengetahuan Ibu terhadap Angka Kejadian Infeksi Soil-Transmitted Helminth pada Siswa SD Negeri 065853 Tegal Sari Mandala Kecamatan Medan Denai Tahun 2018 - Radika Fadhillah; Nelli Murlina (UMSU, 2020)
Introduction: Helminth infection is a major public health problem of those who living in developing countries. Helminth infection on children commonly caused by soil transmitted helminth (STH). The infections are influenced by low level of mother’s knowledge will affect to poor parenting especially the parenting that can avoid her child from helminth infection. This study was aimed to find the correlation between level of mother’s knowledge towards the occurrence of STH infection on students at SDN 065853 Tegal Sari Mandala Kecamatan Medan Denai. Method: This study is descriptive analitic study and uses cross-sectional design. Subjects of this study were 109 students of SDN 065853 Tegal Sari Mandala Kecamatan Medan Denai. Data were collected using validated questionnaire and identification of feces was conducted at parasitology laboratory of Faculty of Medicine, University of Muhammadiyah Sumatera Utara (UMSU). Results: The prevalence of soil transmitted helminth infection attain 59,6% and level of mother’s knowledge which are enough level is 47 people (43,1%). Conclusion: There is meaningfull correlation between level of mother’s knowledge with prevalence of soil transmitted helminth infection in students of SDN 065853 Tegal Sari Mandala Kecamatan Medan Denai (p=0,002).